1998
DOI: 10.1089/thy.1998.8.203
|View full text |Cite
|
Sign up to set email alerts
|

mRNA Levels of Membrane-type 1 Matrix Metalloproteinase (MT1-MMP), MMP-2, and MMP-9 and of their Inhibitors TIMP-2 and TIMP-3 in Normal Thyrocytes and Thyroid Carcinoma Cell Lines

Abstract: Thyroid cancer can degrade basement membranes and invade tissues. This depends on a cascade of matrix metalloproteinases involving membrane-type 1 matrix metalloproteinase (MT1-MMP), MMP-2, and MMP-9. We analyzed the expression and role of these MMPs and their specific inhibitors TIMP-2 and TIMP-3 in human highly purified thyroid epithelial, C 643, HTh 74, SW 1736, and 8505 C thyroid carcinoma and thyroid-derived fibroblast cell cultures. The effect of phorbol-myristate acetate (PMA), and of the inflammatory c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
0
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 26 publications
6
27
0
2
Order By: Relevance
“…Induced expression occurred over a longer time scale (after 6 h) than the increase in cell-associated MT-MMP activity that was inferred from the presence of the 64 kDa and 62 kDa MMP-2 forms. This is similar to effects of PMA and other angiogenic stimuli on MT1-MMP expression [25,26,35] Another recent study [19] has argued that thrombin activation of pro-MMP-2 in human foreskin microvascular endothelial cells is independent of MT1-MMP. In part, these differences may simply reflect differences in the cell types, since HUVECs spontaneously generate a low level of intermediate and fully active forms of MMP-2 without stimulation.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Induced expression occurred over a longer time scale (after 6 h) than the increase in cell-associated MT-MMP activity that was inferred from the presence of the 64 kDa and 62 kDa MMP-2 forms. This is similar to effects of PMA and other angiogenic stimuli on MT1-MMP expression [25,26,35] Another recent study [19] has argued that thrombin activation of pro-MMP-2 in human foreskin microvascular endothelial cells is independent of MT1-MMP. In part, these differences may simply reflect differences in the cell types, since HUVECs spontaneously generate a low level of intermediate and fully active forms of MMP-2 without stimulation.…”
Section: Discussionsupporting
confidence: 69%
“…Augmentation of the level of the 64 kDa intermediate form by treatment of cells with PMA or con A (both of which increase the expression of MT1-MMP [25,30]), led to a corresponding increase in the 63 kDa species in medium from cells exposed to thrombin together with either con A or PMA as compared with HUVECs treated with thrombin alone. The 64 kDa species was not observed in the conditioned medium of HUVECs stimulated with thrombin, or combinations of thrombin and PMA or con A.…”
Section: Discussionmentioning
confidence: 99%
“…IL-8, an angiogenic cytokine secreted from glioma cells, is thought to be a causative cytokine of hypervascularity in malignant glioma (23), thus contributing to the glioma progression. On the other hand, IL-6 and IL-8 have been suggested to have a role in cancer cell invasion by the induction of MMPs (matrix metalloproteinase) (32)(33)(34). Degradation of collagen in the extracellular matrix mediated by MMPs has been suggested to play an essential role in cancer invasion (35).…”
Section: Discussionmentioning
confidence: 99%
“…Normal thyrocytes in culture express mRNA for MMP-2, whereas thyroid anaplastic carcinoma cell lines express MMP-1, -2 and -9 and TIMP-1, -2 and -3 mRNA in vitro (Aust et al 1997). Interestingly, the thyroid cell type that secretes the greatest amounts of MMPs are fibroblasts, and these are stimulated by phorbol esters to increase secretion of a number of MMPs, including MMP-2 and -9 (Hofmann et al 1998). This would concur with a previous study that found expression of MMP-2 mRNA predominantly restricted to fibroblasts in thyroid tumours (Zedenius et al 1996).…”
Section: Matrix Metalloproteinases (Mmps)mentioning
confidence: 99%